Rhetoric, technology, and the virtues - Colton, Jared S.; Holmes, Steve, 1983- (Utah State University Press, 2018)
"Argues that virtue ethics supports postmodern criticisms of rational autonomy and universalism, while enabling a discussion of actual ethical behaviors that digital users form through particular communicative ends and various rhetorical purposes. Extending Aristotle's framework of hexis through the framework of contemporary virtue ethicists and political theorists"--Provided by publisher